If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9(4x + -3) = 3(12 + 6) Reorder the terms: 9(-3 + 4x) = 3(12 + 6) (-3 * 9 + 4x * 9) = 3(12 + 6) (-27 + 36x) = 3(12 + 6) Combine like terms: 12 + 6 = 18 -27 + 36x = 3(18) Multiply 3 * 18 -27 + 36x = 54 Solving -27 + 36x = 54 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '27' to each side of the equation. -27 + 27 + 36x = 54 + 27 Combine like terms: -27 + 27 = 0 0 + 36x = 54 + 27 36x = 54 + 27 Combine like terms: 54 + 27 = 81 36x = 81 Divide each side by '36'. x = 2.25 Simplifying x = 2.25
| 3m+2(m+2)=20-(2m-5) | | 6(t-3)+6t=4(3t+3)-11 | | -(3y+1)-(-2y-4)=0 | | 17(t-5)+4t=7(3t+3)-12 | | 9+19n-4=5n+53-2n | | 3+11s-1=4s+56-2s | | -(3y+1)-(-2y-6)=0 | | y-12=-5 | | x-8.9=-6.3 | | 4+x=290 | | h=16t^2+32t+1008 | | y=-5(4)-2 | | 2y=-x+3 | | 9k-4k-8k=-15 | | 1.6q-3.5-4.5q=3.9q-1.2 | | y=-5(-2)-2 | | -3(3b+3)+(10b-9)=0 | | 10y=-5x+15 | | 4x^2+25-9=0 | | -9=4w-3 | | -10.2x=40.8 | | 5p+4p=81 | | x^2+36-4=0 | | 9z+6z=75 | | x(7x+15)=0 | | -7.9X=47.4 | | 6=7z+6 | | 12(2x-7)=4(6x+6) | | -(5y+1)-(-4-8)=5 | | 18x^3=15x^2+12x | | -2+x^2=0 | | x+(x+1)=69 |